Investigation of Recycling Behavior of Lithium Iron Phosphate Batteries with Different Thermal Pre-Treatments - Hüseyin Eren Obuz; Firat Tekmanli; Luka Nils Mettke; Marius Müller; Bengi Yagmurlu (Materials Proceedings)
Lithium iron phosphate (LFP) batteries are becoming a growing trend as a consequence of EU regulations and their advantages over nickel manganese cobalt (NMC) batteries. The use of LFP batteries is expected to increase considerably globally, creating an enormous waste problem. Battery recycling is emphasized in the EU’s battery laws, especially for lithium. Proper recycling of LFP batteries reduces environmental damage and supports the circular economy. Graphite and lithium are acknowledged as essential raw minerals. Recycling LFP batteries can be accomplished using pyrometallurgical and hydrometallurgical techniques. This study investigates the impact of thermal pre-treatments on flotation and leaching to produce an efficient recycling process.